2019
DOI: 10.22377/ijgp.v13i2.2492
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction:Oxidative stress may lead to a number of diseases such as atherosclerosis, nephrotoxicity, liver cirrhosis, cancers, diabetes, and Alzheimer disease. Medicinal plants are an important source of antioxidants. Therefore, the antioxidant potential of Dillenia bracteata was evaluated in the present study. Materials and Methods: The coarse powder of leaf of Dillenia bracteata (Dilleniaceae) was extracted in Soxhlet apparatus, with ethanol (90%) and ethanolic extract of D. bracteata (EEDB) was further p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Ethanol extract of D. indica has an inhibition percentage of 97.10±0.01% (Saha et al 2009;Rahayu et al 2019). Ethanolic extract of D. bracteata leaves inhibited 74% with DPPH (Shama et al 2019). Patel et al (2020 reported that the ethanolic extract of D. pentagyna leaves has an inhibition percentage of 76.46± 1.58% with the DPPH method.…”
Section: Antioxidant Activity Dpph Methods (22-diphenyl-1-picrylhydra...mentioning
confidence: 96%
See 4 more Smart Citations
“…Ethanol extract of D. indica has an inhibition percentage of 97.10±0.01% (Saha et al 2009;Rahayu et al 2019). Ethanolic extract of D. bracteata leaves inhibited 74% with DPPH (Shama et al 2019). Patel et al (2020 reported that the ethanolic extract of D. pentagyna leaves has an inhibition percentage of 76.46± 1.58% with the DPPH method.…”
Section: Antioxidant Activity Dpph Methods (22-diphenyl-1-picrylhydra...mentioning
confidence: 96%
“…Thooptianrat et al (2017); Putra et al (2019); Yakop et al (2020) showed that ethyl acetate extract of D. suffruticosa leaves contains tannins, polyphenols, and triterpenoids and triterpenoids. On the other hand, Shama et al (2019) reported that the ethanolic extract of D. bracteata contains glycosides, carbohydrates, triterpenoids, proteins, amino acids, gums, mucilages, and flavonoids.…”
Section: Phytochemical Testmentioning
confidence: 99%
See 3 more Smart Citations